ANALYSIS OF WIND ENERGY POTENTIAL IN THE AREA OF TOREA AIRPORT, FAKFAK, WEST PAPUA - Naomi Lembang; Herman HR; Khairunnisa Mansur; Yulan Yulan (Jurnal Media Elektrik, 2025)
One of the renewable energy that is growing rapidly in the world today is wind energy. Wind energy is a very flexible energy. The wind potential of the Torea Fakfak Airport area, West Papua is quite strong considering that planes often fail to take off due to strong winds, wind measurement data collection is located in a coastal area, so this study aims to evaluate the potential of wind energy in the Torea Fakfak area as an alternative renewable energy source. This study involves analyzing wind speed data for one month using an anemometer measuring device installed in a strategic location, this measurement was only carried out at a height of 2 meters. The results show that the average wind speed in the area reaches 2.6 m/s. The electrical energy power obtained in these conditions is 79.77517 watts or in 24 hours the power generated is around 1,914.60 watts. The power generated is not large but the energy can be optimized for the needs of public facilities such as street lights and also the needs of equipment such as TVs, laptops, small refrigerators and others Keywords: Wind Potential, Electrical Energy, Wind Speed, Sea Breeze.